Continuous Monitoring Reveals Protective Effects of N‐Acetylcysteine Amide on an Isogenic Microphysiological Model of the Neurovascular Unit (Small 32/2021). Issue 32 (12th August 2021) - Matthiesen, Isabelle; Voulgaris, Dimitrios; Nikolakopoulou, Polyxeni; Winkler, Thomas E.; Herland, Anna
Abstract : Microphysiological Systems In article number 2101785, Thomas E. Winkler, Anna Herland, and co‐authors describe a microphysiological blood‐brain barrier model that captures the multicellular interactions of iPS‐derived cells. The integrated electrical sensors, facilitated by PDMS‐free fabrication, allow for real‐time monitoring of how the barrier responds to oxidative stress and antioxidant prophylaxis.